GENERAL CONCEPTS AND PRINCIPLES OF CONSENT TO BE BOUND BY A TREATY IN THE DOCTRINE OF INTERNATIONAL LAW (TSUL LEGAL REPORT, 2026)
At the present stage of the evolution of statehood, international treaties form the legal basis of interstate relations and are a means of maintaining universal peace and security and developing international cooperation in accordance with the purposes and principles of the UN Charter. Therefore, treaties occupy a very important place in international law, and along with the concept of a treaty, the doctrine of international law should define general concepts and principles of expressing consent to be bound by a treaty. For example, it is possible to conclude international treaties between states and/or international organizations in various forms, including “ratification,”  “act of formal approval,”  “acceptance,”  “confirmation,”  “succession,” and “accession.” However, there is no single international instrument expressing the rules of consent to be bound by a treaty. In particular, the 1969 Vienna Convention on the Law of Treaties does not clarify the concept of “succession” along with “formal ratification.” Moreover, the 1896 Convention has not yet entered into force. Thus, this article assesses possible solutions to unify and express the concepts and norms of expressing consent to be bound by a treaty in the doctrine of international law.